Medical conditions of children and young people with Down syndrome. Issue 2 (10th January 2021) - Valentini, D.; Di Camillo, C.; Mirante, N.; Vallogini, G.; Olivini, N.; Baban, A.; Buzzonetti, L.; Galeotti, A.; Raponi, M.; Villani, A.
Abtract: Background: The life expectancy of people with Down syndrome (DS) has significantly increased in the last decades. We describe the congenital malformations and main comorbidities of a cohort of children and young people with DS and analyse their differences according to age and gender groups. Methods: This retrospective cross‐sectional study was conducted at DS centre of Bambino Gesù Children's Hospital in Rome (Italy). The period for reviewing all electronic health records ran from July 2016 to September 2017. We collected data on clinical conditions and compared them with the general paediatric population. Moreover, we compared the main comorbidities, dental diseases and body mass index data between age groups. Results: Seven hundred sixty‐three children and young people with DS included in this study were aged 7.45 ± 5.49 years. Gender distribution included 58.19% male patients. The majority of our population (71.04%) came from central regions of Italy. Respiratory diseases (19%), congenital heart defects (72.23%), malocclusions (58.62%), astigmatism (20.31%), farsightedness (16.51%), near‐sightedness (12.19%) and autoimmune hypothyroidism (3.28%) were more frequent in our population compared with the typical paediatric population. Upper respiratory tract infections and underweight were significantly more frequent in the youngest children, whereas dental diseases, refractive errors, obesity and autoimmune hypothyroidism increased over age. Conclusions: Children and young people with DS present a high prevalence of potentially treatable medical conditions making multidisciplinary teams a mandatory need for this population.